PEMIKIRAN POLITIK DALAM ISLAM - Wahid, Abd. (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2010)
Muslim theologians, jurists and philosophers have developed Islamic po-litical thought along history. The classic theologians of Syiâah, Khawarij,Murjiâah, Muâtazilah and Asyâariyah schools focus their political thoughton the question of who has the right to rule the Muslim community afterthe death of the prophet Muhammad. Among the jurists, al-MÃ¢wardÃ® ar-gues that the aim of establishing a state is to continue the prophetic mis-sion, namely to protect religion and to enhance the welfare of the Muslimcommunity. Finally, the Muslim philosopher and historian, Ibn KhaldÃ»nargues that the state should be based on group feeling (âashabiyah), and thegroup feeling based on religion should be at the top of the other kinds ofgroup feeling.